Understanding the experience of time for dementia education programme on undergraduate radiography students. (May 2023) - Wonnacott, L.; Banerjee, S.; Hicks, B.; Daley, S.
Abstract: Introduction: Dementia is a global health priority, which requires the healthcare workforce to have the necessary attitudes and skills to deliver person-centred care to people with dementia. Radiographers have frequent contact with people with dementia, and undergraduate training is potentially an optimal time to deliver dementia education. Time for Dementia is an education programme in which undergraduate healthcare students visit a person with dementia and their carer over a two-year period to gain an in-depth understanding of the condition. The aim of this study was to understand undergraduate radiography students' experiences of undertaking the Time for Dementia (TFD) programme. Methods: Two focus groups were undertaken with 14 radiography students who were half-way through the TFD programme. Data was analysed using thematic analysis. Results: Three key themes were constructed from the analysis: A Holistic Learning Experience, Transferring Learning into Practice and Preparedness & Expectations. Participants discussed the value from learning directly from people with dementia and their carers, reporting an increase in their awareness and understanding of dementia as well as the impact of caring for somebody with the condition. Participants were able to identify learning to take into practice such as person-centred care, compassion, and patience. Challenges to learning were also identified. Conclusions: This study suggests that a longitudinal, experiential education programme provides radiography students with the opportunity to develop a more holistic understanding of dementia and the impact it may have on the individual and their family members. Implications for practice: Experiential dementia teaching is of value to radiography students, however preparation and learning support should fit with previous personal and teaching experience.